Improving information and communication to boost inclusion and self-reliance for urban refugees - Buffoni, L; Hopkins, G (Refugee Studies Centre, University of Oxford, 2020)
Evidence from a refugee community-led assessment in Nairobi shows that communication and information flows must be improved to build sustainable resilience and self-reliance among urban refugees.